Perspectives on disability & rehabilitation contesting assumptions, challenging practice - Hammell, Karen Whalley (Churchill Livingtone Elsevier, 2006)
It explores issues that are central to rehabilitation, such as the nature of the body, the idea of independence, the rehabilitation process, evidence-based practice and client-centred practice. Seeking always to ground theoretical ideas in the realities of every-day rehabilitation practice, and drawing from a wealth of research evidence, the book continually examines the implications of these perspectives for the education, practice, service delivery, research and theoretical development of the rehabilitation professions.